Planned stagnation? The economic plan vs. reality in the Czechoslovak railway sector of the 1970s and 1980s - Tomáš Nigrin (Review of Economic Perspectives, 2018)
The article deals with the state of the railway sector in a centrally planned economy in Czechoslovakia in the 1970s and 1980s. It compares the “to-be” position of the Czechoslovak state railway with the real situation in the railway sector. The Czechoslovak railway sector changed a lot during the two analysed decades – it lost its superior position to road transport and showed evident signs of stagnation, even though a big part of economy was dependent on the railway transport. The position of railway transportation had weakened within the two decades and the country lost its stage by stage initiative in modernisation of the railway sector. The railway sector lost its pre-1970s sovereignty in transport and had become more dependent on the general situation of the Czechoslovak economy. It was the reason for stagnation as a result of development of the railway sector in late socialism in Czechoslovakia.
Keywords: R42; N70; P21; 330; Czechoslovakia; Czechoslovak State Railway; centrally planned economy; socialism